Antibody-mediated Rejection of Kidney Allografts Following COVID-19: A Report of Two Cases (Iranian Journal of Kidney Diseases, 2022)
Increased risk of graft rejection could be the consequence of COVID-19 in kidney transplant recipients (KTRs). We report two cases of kidney transplant (KT) with stable graft function who experienced antibody-mediated rejection (ABMR) following recovery from COVID-19. It seems that reduced immunosuppression during the acute illness, is the main explanation for post-COVID-19 ABMR. However, the inflammatory state associated with COVID-19, as well as direct cytopathic effects of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can predispose the kidney allograft to rejection. There is no definite guideline for the modification of immunosuppressives during COVID-19 in kidney transplant recipients. However, re-institution of full-dose immunosuppressives soon after recovery from COVID-19 and frequent outpatient follow-up visits are recommended.  DOI: 10.52547/ijkd.7176